Communication Skills and Communicative Autonomy of Prelinguistic Deaf and Hard-of-Hearing Children: Application of a Video Feedback Intervention - Wadnerkar Kamble, Meghana; Lam-Cassettari, Christa; James, Deborah M. (Frontiers in Psychology, 2020)
Background and Aim: Evidence on the efficacy of parenting interventions to support communication development in deaf and hard-of-hearing children is emerging. In previous research, we showed that parental participation in a video feedback-based intervention enhanced parental self-esteem, and emotional availability to their deaf and hard-of-hearing children. This paper investigates the impact of the intervention on development of the children’s prelingual communication skills and autonomy. Evidence on the efficacy of parenting interventions to support communication development is warranted. Methods: Sixteen hearing parents with a prelingual deaf and hard-of-hearing child (Mage= 2.05 years, SD= 1.77) were recruited by self-selection from paediatric audiological services, and randomly stratified into Intervention First, and Waiting-List Groups. Families completed three sessions of Video Interaction Guidance in their homes. Designed for maximal inclusion, the sample comprised of children with complex developmental and social needs. Primary inclusion criterion was child’s prelingual status (<50 signed/spoken words), which was established using speech and language therapy reports. Child communicative autonomy was assessed from a 20-minute free play video-recording using a gold standard measure for deaf and hard-of-hearing children (Tait) before and after the intervention. Results: Mann-Whitney U test indicated no significant difference between the two groups. The groups were collated and Wilcoxon Signed Rank test with Time (Pre/Post intervention) as a repeating variable was run. A significant increase was shown child’s communicative autonomy (Z -3.517, p< .0001, d=0.62), and decrease in child’s no-responses (Z -3.111, p< .005, d=0.55) were seen. There was no significant difference in the overall number of turn-taking between the parent and child. Indicating differences in the quality of the parent-child interactions, not the quantity. Conclusion: This study adds to the emerging evidence for parenting interventions with deaf and hard-of-hearing children. We hypothesise that the video feedback intervention with its focus on emotional availability, created space for the child to show increased communicative autonomy during parent-child interactions. Communicative autonomy is a long-term predictor of communication and linguistic development in deaf and hard-of-hearing children, and its conceptual underpinning makes it a good early measure of relational agency. Results can inform wider interventions that focus on quantity of the parent-child communication.